The Implementation of Al-‘Adl Method According to Muhammad Yusuf Al-Qaradhawi in the Context of Contemporary Islamic Family Law: Implementasi Metode Al-‘Adl Menurut Yusuf al-Qardhawi Dalam Konteks Hukum Keluarga Islam Kontemporer - Salsabila, Saila; Sholihin, Rahmat (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Dr. Muhammad Yusuf al-Qaradhawi is a famous scholar who was born in western Egypt in 1926. He studied at al-Azhar University and productively wrote many works in various fields using the al-'Adl method as one of the significant contributions to the advancement of science. The al-'Adl method is a concept based on the Qur'an and Sunnah with a strong methodological framework and is able to produce a logical balance model (al-Tazawun) according to the size, scale of the tasyri' spirit and human ratio. Al-'Adl is a characteristic of al-Qaradhawi's view with an emphasis on the priority of actions that are in line with the Qur'an and its evidence, participating in opening up thinking, correcting its methodology and laying a strong foundation for the development of fiqh as the will of the Qur'an. This research uses a literature study method with a qualitative approach to examine the al-'Adl method and its application in the context of contemporary family law. The results of the study show that al-Qaradhawi provides answers to various problems of Islamic family law in the form of contemporary fatwas using the ijtihad al-'Adl method in his book entitled Hadyul Islam Fatawi Muashirah. Some of the issues that are of concern in this study include: The law of dowry and its wisdom, the law of marrying a former mother in law whose child has not been intimate with, the problem of the amount of inheritance, inheritance for disobedient children, and the amount of milk that prohibits marriage. al-'Adl reflects the alignment of Islamic law with the spirit of justice and balance.